Ergonomic diagnosis of postural changes and ergonomic risk assessment of a left-handed user in the operation of a drill press, using the REBA, RULA and OCRA Checklist methods - Obando Herrera, Fabio Eduardo (2020)
This investigation is a study aimed at assessing posture and evaluating the risk of musculoskeletal injuries (MSI) in upper limbs of mechanical engineering students at the Universidad Politécnica Salesiana in Quito, Ecuador. Through a descriptive study of ten students with an average age of 19.8 ±1.23 years and average drill-use experience of 1.9 ±1.3 months, ergonomic risk was assessed using REBA (Rapid Entire Body Assessment), RULA (Rapid Upper Limb Assessment), and OCRA (Occupational Repetitive Action) Checklist methods. Previously, Harris and Edinburgh tests were used to evaluate laterality, which resulted in a 100% consistently left-handed population (p<0.05). Upper limb joint angles were measured using photometry and the free software Ruler, establishing a database for ergonomic risk assessment. Next, Pearson’s correlation was used to compare the operator’s laterality with each ergonomic evaluation method. Additionally, other variables analyzed were the operators’ age and their experience using the drill press, which do not contribute to the risk of MSI. In conclusion, a high risk of MSI exists for left-handed users when they operate a drill press, and this risk increases with their degree of laterality.